G64(P) What evidence is available to support the development of a regional specialist neuro-rehabilitation outreach service. (May 2019) - Bhowaneedin, A; Smith, H; Deeley, H; Reyes Payeras, C; Keating, O; Smallbone, T; Wright, I; Sharples, PM
Abstract : Background: The WHO recognises several specialist rehabilitation provision models; in-patient, outpatient and outreach. Intensive early neurorehabilitation is required after severe Acquired Brain Injury (ABI), usually necessitating in-patient care. In the UK, children receiving specialist neurorehabilitation often remain in-patients for long periods because of the lack of appropriate out-of-hospital provision. Aims: To explore feasibility and funding implications of developing a regional specialist neurorehabilitation outreach service to facilitate earlier discharge. Methods: Analysis of data on children receiving in-patient neurorehabilitation at a paediatric Regional Neuroscience Centre (RNSC), 2014–2018. Information concerning therapy provision was obtained from Trust Clinical Information System Suite (CISS). Patient dependency and rehabilitation complexity was assessed by Rehabilitation Complexity Scale–Extended (RCS-E), scored by multi-disciplinary team (MDT) at weekly meetings over 15 months. For modelling purposes, a specialist neurorehabilitation outreach tariff equating to 50% in-patient tariff was assumed. Data analysis was undertaken by linear programming model ( XpressIve©) and Discrete-Even Simulation (Simul8©). Various eligibility criteria for outreach provision were modelled: 1) needing > 1 therapies<3 times/week; 2) Total RCS-E score <9, <11 or<13; 3) Therapy Dependency (TD) +Therapy Intensity (TI) components of RCS-E < 5. Results: 156 children received neurorehabilitation as in-patients over 4 years. Mean age=7.34 years (range 0.1–17). 66 (55%) were male, 53 (45%) female. 84% had ABI, others acquired spinal injury, acute polyneuropathy or somatisation disorders. 52% lived >40 miles from RNSC, 47%>60 min' drive away. 49% were inpatients 1–28 days; 34%, 29–84 days; 18, 85–168 days; 6, >168 days. Patients showed significant functional improvements between admission to neurorehabilitation and discharge (p<0.001). Modelling suggests 14 outreach centres, including RNSC, would be required to permit 78% patients to access specialist neurorehabilitation <30 mins drive from home; 10 centres would permit 92% to access neurorehabilitation <45 min' drive away; 8 centres would permit 96% to access neurorehabilitation <60 min' drive away. Calculations assuming outreach tariff=50% in-patient tariff, and various RCS data models, suggest annual cost savings ranging from £53, 424-£166, 950; calculations based on CISS data, suggest average savings of £1 05 596 per year (range £98, 500-£113, 526). Conclusion: Modelling supports the feasibility and affordability of specialist neurorehabilitation outreach provision, although efficacy remains uncertain.